CONTROVERSIES IN THE LEGAL REGULATION OF SAME-SEX COUPLES IN THE REPUBLIC OF SERBIA IN LIGHT OF INTERNATIONAL LAW AND COMPARATIVE LAW - Darko; Jović-Prlainović, Olga (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Marriage and familiy are institutions which are continually evolving. Social reality points to the fact that the traditional concept of marriage does not have the capacity to recognize the full complexity of interpersonal relationships. Hence the aspiration for marriage to be equalized with common law marriages, including long term unions between individuals of the same sex. The European Court of Human Rights has greatly contributed to the improvement of the legal position of same-sex partners. To date, the European Court has not equalized same-sex unions with marriage, however it has foreseen that same-sex couples have to be legally recognized so that their relationship would be protected. Member states are not obliged to recognize same-sex marriages, however they have an obligation to institutionalize same-sex unions, for the purpose of protecting the rights and interests of those individuals who are part of them. The intent is to legally regulate personal and the property rights of same-sex couples, in accordance with the obligations of the Republic of Serbia which emanate from the application of the European Convention on Human Rights. However, the overall impression is that the Draft Law on Same-Sex Unions does not contain consistent and well thought out solutions. Analyzed from the aspect of family law, there are significant criticisms with respect to the currently proposed draft law, particularly with regards to the exercising of parental rights. Although the Draft Law does not foresee the possibility of adopting children, the question is raised as to the basis on which a partner of the child’s parent obtains authorities vested by way of parental rights. A belief remains that due to the far-reaching consequences, the process of legally regulating same-sex unions must evolve with great care, especially as this remains an extremely controversial topic in Serbian society.